Trigeminal neuralgia in multiple sclerosis: Prevalence and association with demyelination. (3rd April 2020) - Laakso, Sini M.; Hekali, Oskari; Kurdo, Goran; Martola, Juha; Sairanen, Tiina; Atula, Sari
Abstract: Objectives: The association of trigeminal neuralgia (TN) with multiple sclerosis (MS) is still widely unaddressed in larger, systematical clinical series. In this study, a cohort of Finnish MS patients was assessed regarding the incidence and prevalence of TN, as well as the presence of demyelinating lesions near the trigeminal ganglion, thus searching for a causative role of MS plaques in TN onset. Materials & Methods: All consecutive patients treated and followed up for MS (ICD‐code G35) in Helsinki University Hospital during 2004‐2017 were identified from the Finnish MS register. A hospital administrative database search was used to identify all patients treated and followed up for TN during the same period. Among the MS patients, head MRI scans available from the diagnostic phase of TN or thereafter were analysed. Results: We identified a total of 2575 patients with MS and 2008 patients with TN. Both diagnoses could be verified for 55 patients, giving a prevalence of 2.1% for TN in MS. The incidence of TN in MS patients was 149/100 000 person‐years (95% CI 108‐190). In the general outpatient population of our neurological department, the incidence of TN was 9.9/100 000 person‐years (95% CI 9.5‐10.3). A demyelinating lesion in the proximity of the trigeminal ganglia was seen for 63% of the 41 patients with relevant MRI data available. Conclusions: Incidence of TN among MS patients was 15‐fold higher than in the general neurological outpatient population, thus in favour of a strong association between MS and TN.